COLOR IN PAINTING - WITH SPECIAL REFERENCE TO PREHISTORIC TIMES MADHYA PRADESH: चित्रकला में रंग - प्रागैतिहासिक काल मध्यप्रदेश के विशेष संदर्भ में - Jain, Sunita (International Journal of Research -GRANTHAALAYAH, 2014)
Color is prominent among the elements that provide expressive strength to the painting. Color has an important role in painting. Colors provide adequate support to the basic surface on which the painter paints, based on these, the artwork provides mental satisfaction. A composition created by the basis of color is able to achieve its own characteristics. Through color, the painter softens his work. The sensitivity of a painter’s imaginary picture depends very much on color. The more music is full, appropriate and balanced the use of color, the deeper will be its effect on the human psyche. चित्रकला को अभिव्यक्तिगत सार्मथ्य प्रदान करने वाले तत्वों में रंग प्रमुख है। चित्रकला में रंग की अत्यन्त महत्वपूर्ण भूमिका है। चित्रकार जिस आधारभूत सतह पर चित्रांकन करता है उसमें रंग उसकी पर्याप्त सहायता करते हैं इन्हीं के आधार पर कलाकृति मानसिक सन्तुष्टि प्रदान करती है। रंग का आधार पाकर बनाई गई रचना अपने अभिष्ट को पाने में समर्थ होती है। रंग के माध्यम से चित्रकार अपनी कृति को कोमल बनाता है। चित्रकार का बिम्ब-विधान चित्र सुलभ संवेदनशीलता बहुत कुछ रंग पर निर्भर करती है। रंग का प्रयोग जितना संगीत पूर्ण, उचित और सन्तुलित होगा मानव के मानस पटल पर उसका प्रभाव उतना ही गहरा होगा।